Elongation Factor 2 Kinase Is Regulated by Proline Hydroxylation and Protects Cells during Hypoxia - Moore, Claire E. J.; Mikolajek, Halina; Regufe da Mota, Sergio; Wang, Xuemin; Kenney, Justin W.; Werner, Jörn M.; Proud, Christopher G. (Molecular and cellular biology, 2015)
Protein synthesis, especially translation elongation, requires large amounts of energy, which is often generated by oxidative metabolism. Elongation is controlled by phosphorylation of eukaryotic elongation factor 2 (eEF2), which inhibits its activity and is catalyzed by eEF2 kinase (eEF2K), a calcium/calmodulin-dependent α-kinase. Hypoxia causes the activation of eEF2K and induces eEF2 phosphorylation independently of previously known inputs into eEF2K. Here, we show that eEF2K is subject to hydroxylation on proline-98. Proline hydroxylation is catalyzed by proline hydroxylases, oxygen-dependent enzymes which are inactivated during hypoxia. Pharmacological inhibition of proline hydroxylases also stimulates eEF2 phosphorylation. Pro98 lies in a universally conserved linker between the calmodulin-binding and catalytic domains of eEF2K. Its hydroxylation partially impairs the binding of calmodulin to eEF2K and markedly limits the calmodulin-stimulated activity of eEF2K. Neuronal cells depend on oxygen, and eEF2K helps to protect them from hypoxia. eEF2K is the first example of a protein directly involved in a major energy-consuming process to be regulated by proline hydroxylation. Since eEF2K is cytoprotective during hypoxia and other conditions of nutrient insufficiency, it may be a valuable target for therapy of poorly vascularized solid tumors.